SCIENTIFIC AND CREATIVE ACTIVITY OF ASHTARKHANI ABDULAZIZKHAN AND SUBHONQULIKHAN - Nasrilloyev Karimjon; Shokulov Farrukh (International Scientific and Current Research Conferences, 2024)
This article describes the scientific and creative activities of Abdulaziz Khan and Subhankuli Khan, representatives of the Asharkhanid dynasty, who ruled the Bukhara Khanate, and their relations with scholars.